Control of Aedes mosquito populations using recombinant microalgae expressing short hairpin RNAs and their effect on plankton - Fei, Xiaowen; Xiao, Sha; Huang, Xiaodan; Li, Zhijie; Li, Xinghan; He, Changhao; Li, Yajun; Zhang, Xiuxia; Deng, Xiaodong (PLOS Neglected Tropical Diseases, 2023)
Author summary A new low-cost strategy was developed to control vector mosquitoes safely. Chlorella was genetically modified to produce siRNA targeting the mosquito chsa gene, inhibiting gene expression after the larval stage. The inhibition prevented metamorphosis with high larval mortality in both Aedes aegypti and Aedes albopictus. The recombinant Chlorella performed well in the simulated field trials but impacted plankton populations in the released water, which indicates that the technology requires further optimization for field use. This approach is promising for biorational mosquito control to prevent mosquito-borne diseases.